Proof of marital seizure against joint property in a marriage resulting from divorce (A case study of decisions no. 533/Pdt.G/2021/Pa.Bn And No. 561/Pdt.G/2025/Pa.Krw) - Rikal, Rikal; Muslih, Akhmad; Wafiya, Wafiya (Privietlab, 2025)
The marital beslag plays an important role in protecting common property. The urgency of submitting a marital beslag request was to protect the integrity of the communal property so that, during the process, neither the husband nor the wife could transfer the communal property to a third party. Sometimes, the marital beslag request might have been granted or denied by the judge. The purpose of this research was to understand and analyze the reasons why judges did not grant marital beslag requests, to understand and analyze the evidence of the marital beslag submitted by the plaintiff so that it could be accepted by the judge, and to examine and analyze Religious Court Decision Number 533/Pdt. G/2021/PA.Bn and Decision No. 561/Pdt. Bn. G/2025/PA.Krw regarding marital status. This study employs normative legal research. The research approach used in this thesis is legislative, conceptual, and case-based. The analysis results indicate that (1) In Decision Number 533/Pdt. G/2021/PA.Bn, a marital beslag could not be granted because the lawsuit was declared obscuur libel (vague/unclear), thus formally not meeting the requirements of legal proceedings (Article 8 RBg jo. Article 118 HIR). Meanwhile, in Decision No. 561/Pdt. G/2025/PA.Krw, the marital beslag was denied because the divorce lawsuit as the main matter was not materially proven, so the matter of joint property along with its marital beslag was automatically not accepted; (2) The requirements for accepting marital beslag are: the lawsuit must not be vague, the object of the dispute must be described in detail; there must be authentic evidence demonstrating that the property is joint property acquired during the marriage; there must be urgent reasons to protect the property from potential transfer or concealment; and the seizure must not harm third parties. Failure to meet these requirements, both formally and materially, results in the denial of the marital beslag request. The rejection of marital beslag in Decision Number 533/Pdt. G/2021/PA.Bn and Decision No. 561/Pdt.G/2025/PA.Krw emphasizes that a request for marital beslag could only be granted if it met the formal and material requirements according to the provisions of civil procedural law.